Varying outcomes of triple-negative breast cancer in different age groups - prognostic value of clinical features and proliferation - Korpinen, Katarina (My University, 2022)
Breast cancer is a heterogeneous disease presenting with various molecular subtypes. Compared to the other subtypes, triple-negative breast cancer (TNBC) affects younger patients and is associated with more aggressive course of disease. Due to the lack of Erb-B2-amplification as well as both estrogen and progesterone receptor expression, TNBC is considered as a therapeutic challenge. Currently treatment decisions are based on traditional prognostic features including TNM-stage, patient’s age at diagnosis, and to some extent the cancer cell proliferation but no clinically applicable biomarkers are available for identifying the prognosis of individual TNBC patients. Uncontrollable proliferation is one of the key features of malignant transformation, and an established prognostic feature projecting tumor biology. The aim of the study was to evaluate combined prognostic impact of traditional clinical features and novel cell-cycle progression associated biomarkers in age-dependent subgroups of TNBC patients. The study comprises 147 TNBC patients diagnosed and treated between 2000–2015 in Turku University Hospital, Turku, Finland. Clinical and complete, up to 18 years, follow-up data as well as tissue material of the representative cancer specimen was obtained from Auria Biobank. The tissue material was arranged in tissue microarrays (TMAs) and eight cell division associated biomarkers were immunohistochemically detected to evaluate their clinical applicability in relation to patient and tumor characteristics. Results of this study emphasize the nature of TNBC as a heterogeneous disease entity with varying courses of disease in different age groups. The established prognostic features, nodal status and Ki-67 predicted survival only when combined with age. Among young patients, lack of basal differentiation was the only feature predicting unfavorable disease outcome. Middle-aged patients showed the most favorable outcome, and concerning cell proliferation, Ki-67 alone was a significant prognosticator among this patient group. Concerning the studied cell cycle-specific biomarkers, geminin, associated with tumor size <2cm, predicted an increased risk of mortality. The study provides additional support for the hypothesis that young TNBC patients comprise a unique disease entity, while elderly patients represent a more coherent subgroup. Therefore, young age should be considered as an additional adverse prognostic feature in therapeutic considerations. Traditional clinical features do not provide optimal prognostic characterization for all TNBC patients, and proliferation, as evaluated using Ki-67 or geminin immunohistochemistry, showed potential in detecting survival differences in subgroups of TNBC.
Keywords: triple-negative breast cancer, prognosis, survival, age, proliferation, Ki-67, Geminin